An Exploration of Factors Associated With Polypharmacy in a Residential Health Care Setting for Older Adults - Lisha M. Ulahannan; Frances Finn; Claire O'Gorman; Martina Gooney (Journal of Gerontological Nursing, 2026)
Purpose: To identify the prevalence of polypharmacy and its association with age, sex, body mass index (BMI), comorbidity, and medication categories in Irish residential health care settings for older adults. Method: This quantitative retrospective study was conducted in a residential health care setting for older adults, with 30 participants aged ≥65 years. Results: Prevalence of hyper-polypharmacy (60%) and polypharmacy (37%) was high. Of participants, 97% were taking medications for central nervous system disorders. The three leading medication classes included analgesics (90%), antidepressants (66%), and laxatives (66%). Due to a relatively small sample size, no statistically detectable association was found between the number of medications and age, sex, BMI, and comorbidities. Conclusion: Provision of education for health care professionals and raising awareness among older adults to reduce polypharmacy and associated risks is important. Although the study is limited by insufficient statistical power due to the small sample size, the study design and methods provide preliminary evidence to inform future large-scale research. Further research in Ireland using larger sample sizes is recommended to determine the significance of polypharmacy in relation to these variables.